Is it true that, for any $1$-form on a $3$-mfld $\alpha$, $\alpha \wedge d\alpha=0$?

I'd argue like $$0=d(0)=d(\alpha \wedge \alpha)= 2d(\alpha)\wedge \alpha$$

since for any $1$-form $\alpha \wedge \alpha=0$, but then there are counterexample like $\alpha= dz+xdy$ on $\Bbb R^3$ s.t. $\alpha \wedge d\alpha\neq0$

Where am I making a mistake?


For $1$-forms $\alpha$ and $\beta$, $$d(\alpha\wedge\beta)=(d\alpha)\wedge\beta-\alpha\wedge(d\beta)$$ so that $$d(\alpha\wedge\alpha)=(d\alpha)\wedge\alpha-\alpha \wedge(d\alpha)=0.$$

  • $\begingroup$ ah, I see when I switch $\alpha$ and $d\beta$ the sign is $+1$ not $-1$ $\endgroup$ – Luigi M Aug 23 '17 at 4:38

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.